2009
DOI: 10.1007/s10549-009-0694-5
|View full text |Cite|
|
Sign up to set email alerts
|

Four polymorphisms in cytochrome P450 1A1 (CYP1A1) gene and breast cancer risk: a meta-analysis

Abstract: Cytochrome P450s are enzymes which catalyze Phase-I metabolism reactions; cytochrome P450 1A1 (CYP1A1) is a member of the CYP1 family and participates in the metabolism of a vast number of xenobiotics, as well as endogenous substrates. Four single nucleotide polymorphisms in CYP1A1 have been studied concerning their potential implication in terms of breast cancer risk: T3801C, T3205C, A2455G (Ile462Val), and C2453A (Thr461Asp); controversy exists regarding their role. This meta-analysis aims to examine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 55 publications
1
47
1
Order By: Relevance
“…P450 polymorphisms may well exhibit race-specific effects [1,12]. As a result, given that the vast majority of data came from Caucasian populations in this meta-analysis, the results may not be safely extrapolated upon Chinese subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P450 polymorphisms may well exhibit race-specific effects [1,12]. As a result, given that the vast majority of data came from Caucasian populations in this meta-analysis, the results may not be safely extrapolated upon Chinese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…homozygous carriers versus 'wild type' and heterozygous carriers grouped together. Separate racespecific analyses were considered in case relevant data existed, according to the algorithm adopted in our previous meta-analyses [10][11][12][13][14]. In case of zero cells, an appropriate continuity correction (addition of 0.5) was implemented [10].…”
Section: Statisticsmentioning
confidence: 99%
“…It is assumed that some genetic polymorphisms might modify the risk of breast cancer by influencing the CYP1A1 enzyme activity (6). Four single nucleotide polymorphisms in CYP1A1 have been identified, including T3801C, T3205C, A2455G (Ile462Val), and C2453A (Thr461Asp) (7). In the present work, the association between breast cancer and CYP1A1 Thr461Asn polymorphism was investigated.…”
Section: Introductionmentioning
confidence: 95%
“…The impact of genetic variants on taxane response is unclear: Several studies did not find any relationship between taxane-related gene polymorphisms and response, while others did [54,55], and the most studied genes have been CYP3A4, CYP2C8 and ABCB1 [56][57][58][59]. Recently, new genome-wide association studies (GWAS) have been reported, searching to correlate data of taxane pharmacogenomics with toxicity [60]; this method enables the simultaneous view on a huge amount of known genetic variation in humans, such as the case of the polymorphism CYP1A1 rs1048943 A/G, in association with the risk of development of breast cancer [61]. No GWAS on taxane outcomes and breast cancer has been published since now.…”
Section: Pharmacogenomic Correlations With Outcomementioning
confidence: 99%